Melanoma Prognosis and Associated Risk Factors: A Retrospective Cohort Study Using Semantic Map Analysis - Simone Cazzaniga; Carole Anouk Zahn; Seyed Morteza Seyed Jafari; Robert Emil Hunger (Medical Journals Sweden, 2023)
The overall patterns of correlations among various melanoma risk factors have not yet been examined. The aim of this study was to assess the impact of different parameters on disease-free and melanoma-related overall survival. A retrospective cohort study was conducted encompassing all patients with a primary cutaneous melanoma diagnosed in a university referral centre. Associations were explored using semantic map analysis, which uses graph theory to find the strongest path of connections between variables. A total of 1,110 melanoma patients (median follow-up 10.6 years) were included. The analysis revealed a clustering of variables around 2 main hubs: Breslow thickness < 1 mm and ≥ 4 mm. Factors connected with high melanoma thickness were: older age, positive sentinel lymph node biopsy findings, presence of ulceration, nodular melanoma type, and light skin phototype. Both disease-free and melanoma-related overall survival were in this cluster and connected with positive sentinel lymph node biopsy and Breslow ≥ 4 mm. Patients with Breslow between 1 and 3.9 mm were also in this cluster and linked with negative sentinel lymph node biopsy, nodular melanoma and safety distance > 10 mm. This semantic analysis confirmed the close link between Breslow thickness, age, sentinel lymph node biopsy findings, skin type, melanoma subtype and prognosis, and provides prognostic information useful for the further stratification and management of patients with melanoma.